2014
DOI: 10.3109/14992027.2014.972522
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of linear and nonlinear otoacoustic emission components to low-dose styrene exposure

Abstract: Low-level styrene exposure may have induced a modification of cochlear functionality as concerns linear and nonlinear OAE generation mechanisms. The lack of change in latency seems to suggest that the OAE components, where generation region and latency are tightly coupled, may not have been affected by styrene and noise exposure levels considered here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
3
4
0
Order By: Relevance
“…Sisto et al (2013) showed indeed that OAE-based tests are capable of discriminating at a statistically signiEcant level the styrene-and noise-exposed groups from a control group of nonexposed subjects, both in the case in which the major exposure was due to styrene, and in the case in which the main potentially ototoxic agent was noise. Similar results were obtained by Tognola et al (2015), using a different OAE quantity, derived from the bispectral analysis of the same TEOAE recordings. In Tognola et al (2015), statistical equivalence in mean age between controls and exposed groups was also guaranteed, whereas in Sisto et al (2013) the very large difference observed between the whole exposed and control groups could have been partly due to aging effects in the workers of the exposed groups.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Sisto et al (2013) showed indeed that OAE-based tests are capable of discriminating at a statistically signiEcant level the styrene-and noise-exposed groups from a control group of nonexposed subjects, both in the case in which the major exposure was due to styrene, and in the case in which the main potentially ototoxic agent was noise. Similar results were obtained by Tognola et al (2015), using a different OAE quantity, derived from the bispectral analysis of the same TEOAE recordings. In Tognola et al (2015), statistical equivalence in mean age between controls and exposed groups was also guaranteed, whereas in Sisto et al (2013) the very large difference observed between the whole exposed and control groups could have been partly due to aging effects in the workers of the exposed groups.…”
Section: Introductionsupporting
confidence: 86%
“…Similar results were obtained by Tognola et al (2015), using a different OAE quantity, derived from the bispectral analysis of the same TEOAE recordings. In Tognola et al (2015), statistical equivalence in mean age between controls and exposed groups was also guaranteed, whereas in Sisto et al (2013) the very large difference observed between the whole exposed and control groups could have been partly due to aging effects in the workers of the exposed groups. To test this possible confounding effect, Sisto et al (2013) had repeated indeed the analysis on a subset of the exposed control group that was statistically equivalent in mean age to the controls.…”
Section: Introductionsupporting
confidence: 86%
“…Noise is the most frequent cause of irreversible sensorineural hearing loss in the workplace. Styrene and other simple aromatic chemicals such as toluene, ethylbenzene, and xylenes have been linked to hearing loss in the workplace, particularly in conjunction with exposure to noise (Fechter 1999;Hormozi et al 2017;Johnson 2007;Johnson et al 2006;Lawton, Hoffmann, and Triebig 2006;Metwally et al 2012;Morata et al 2011;Sisto et al 2016Sisto et al , 2013Śliwińska-Kowalska et al 2005;Tognola et al 2015;Triebig, Bruckner, and Seeber 2009;Triebig et al 2001). The evidence base is reasonably robust for this effect, and supported by a number of high-quality toxicological and mechanistic animal studies (Campo et al 1999(Campo et al , 2001(Campo et al , 2003(Campo et al , 2011(Campo et al , 2014Chen et al 2007;Chen, Tanaka, and Henderson 2008;Chen and Henderson 2009;Loquet, Campo, and Lataye 1999;Fetoni et al 2016;Gagnaire and Langlais 2005;Gagnaire et al 2006;Lataye, Campo, and Loquet 2000;Lataye et al 2001Lataye et al , 2003Lataye et al , 2004Mäkitie et al 2002;Pouyatos et al 2004;Pouyatos, Campo, and Lataye 2005;Venet et al 2015;Wang et al 2...…”
Section: Non-cancer Health Effectsmentioning
confidence: 99%
“…Workers employed in molding were defined as styrene exposure group (S, n = 9, age 28-47 years, tenure 5-26 years) with styrene exposure levels in the order of 20 ppm and noise levels below the action level of 85 dB with a mean of 83 dB (range 80.7-84.2 dB). Slightly different levels were given by Tognola et al (2015): mean 82.4 dB (range 80.7-83 dB). Refinery workers defined as the noise + styrene group (NS) group (n = 6, age 32-52 years, tenure 3-27 years according to Tognola et al 2015) were exposed to lower styrene concentrations by about 1 order of magnitude (according to Tognola et al (2015) ≪ 2.3 ppm), but higher noise levels with a mean of 87.7 dB (range 86.7-88 dB).…”
Section: Non-cancer Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation